Donor corneas misidentified with prior laser in situ keratomileusis - Kang, Shin Jeong; Schmack, Ingo; Edelhauser, Henry F.; Grossniklaus, Hans E. (Cornea, 2010)
To evaluate the rate of donor corneas misidentified as recipients of previous laser in situ keratomileusis (LASIK) surgery in the eye banks.